Missense Mutations Modify the Conformational Ensemble of the α-Synuclein Monomer Which Exhibits a Two-Phase Characteristic - Guzzo, Adrien; Delarue, Patrice; Rojas, Ana; Nicolaï, Adrien; Maisuradze, Gia G.; Senet, Patrick (Frontiers in Molecular Biosciences, 2021)
alpha-synuclein is an intrinsically disordered protein occurring in different conformations and prone to aggregate in beta-sheet structures, which are the hallmark of the Parkinson disease. Missense mutations are associated with familial forms of this neuropathy. How these single amino-acid substitutions modify the conformations of wild-type alpha-synuclein is unclear. Here, using coarse-grained molecular dynamics simulations, we sampled the conformational space of wild-type and mutants (A30P, A53P, and E46K) of alpha-synuclein monomers for an effective time scale of 29.7 ms. To characterize the structures, we developed an algorithm, CUTABI (CUrvature and Torsion based of alpha-helix and beta-sheet Identification), to identify residues in alpha-helix and beta-sheet from C-alpha coordinates. CUTABI was built from the results of the analysis of 14652 selected protein structures using the Dictionary of Secondary Structure of Proteins (DSSP) algorithm. DSSP results are reproduced with 93 % of success for 10 times lower computational cost. A two dimensional probability density map of alpha-synuclein as function of the number of residues in alpha-helix and beta-sheet is computed for wild-type and mutated proteins from molecular dynamics trajectories. The density of conformational states reveals a two-phase characteristic with a homogeneous phase [state B, beta-sheets] and a heterogeneous phase [state HB, mixture of alpha-helices and beta-sheets]. The B state represents 40 % of the conformations for wild-type, A30P and E46K and only 25 % for A53T. The density of conformational states of the B state for A53T and A30P mutants differs from the wild-type one. In addition, the mutant A53T has a larger propensity to form helices than the others. These findings indicate that the equilibrium between the different conformations of alpha-synuclein monomer is modified by the missense mutations in a subtle way. The alpha-helix and beta-sheet contents are promising order parameters for intrinsically disordered proteins whereas other structural properties such as average gyration radius, Rg, or probability distribution of Rg cannot discriminate significantly the conformational ensembles of wild-type and mutants. When separated in states B and HB, the distributions of Rg are more significantly different, indicating that global structural parameters alone are insufficient to characterize the conformational ensembles of the alpha-synuclein monomer.